1979
DOI: 10.2190/gvc0-31dh-w9ln-e8m4
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia Acceptance as Related to Afterlife Belief and Other Attitudes

Abstract: In recent years, euthanasia has become a topic of increased concern. Predictions were made regarding the relationship between attitudes toward euthanasia and various other attitudinal components of death and dying. Information on these attitudes was obtained from fixed-schedule interviews gathered from 331 respondents in Lubbock, Texas. It was found that a favorable attitude toward euthanasia coincided with (1) belief in an afterlife, (2) a less favorable attitude toward euthanasia if relatives make the decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Again, there seems to be conflicting findings. Klopfer and Price (1978-79) expected to find that older people would be more approving of euthanasia; however, they found that younger people were actually more approving. Blendon et al (1992) also found that younger respondents showed stronger support for legalizing euthanasia (79 percent) than did older respondents (53 percent).…”
Section: Age and Attitude Toward Assisted Suicidementioning
confidence: 95%
“…Again, there seems to be conflicting findings. Klopfer and Price (1978-79) expected to find that older people would be more approving of euthanasia; however, they found that younger people were actually more approving. Blendon et al (1992) also found that younger respondents showed stronger support for legalizing euthanasia (79 percent) than did older respondents (53 percent).…”
Section: Age and Attitude Toward Assisted Suicidementioning
confidence: 95%
“…The current study investigated how public attitudes toward euthanasia were influenced by (1) the method of death to be employed (e.g., life-support withdrawal vs. lethal injection); and (2) the identity of the patient making the request (e.g., stranger vs. self). Most of the studies reviewed did not explicitly compare acceptance of passive versus active euthanasia (Adams, Bueche, & Schvaneveldt, 1978; Bosmann et al, 1987; Ho & Penney, 1991; Jorgenson & Neubecker, 1980/1981; Shuman, Fournet, Zelhart, Roland & Estes, 1992), and many failed to provide a clear definition of both (Devins, 1980/1981; Klopfer & Price, 1979; Sawyer, 1982; Singh, 1979; Wade & Anglin, 1987). No previous work has focussed on the self versus unknown other distinction.…”
Section: The Present Studymentioning
confidence: 99%
“…These are the only consistent findings reported in the literature. Inconsistent findings are reported with regard to associations between gender and the willingness to prolong life (Klopfer and Price, 1978;Preston and Williams, 1971), age (Jorgenson andNeubecker, 1980-1981;Klopfer and Price, 1978;Preston and Williams, 1971), and health status (Cohen-Mansfield, Droge, and Billig, 1992;Danis et al, 1988;Maguire, 1974). The inconsistent findings indicate weak associations and/or represent the current complexity in the terminology of concepts relating to terminating or prolonging life.…”
mentioning
confidence: 99%